2016
DOI: 10.3892/etm.2016.3292
|View full text |Cite
|
Sign up to set email alerts
|

Bushen-Qiangdu-Zhilv decoction inhibits osteogenic differentiation of rat fibroblasts by regulating connexin 43

Abstract: Abstract. Bushen-Qiangdu-Zhilv (BQZ) decoction is a traditional Chinese medicinal compound widely used for treating ankylosing spondylitis (AS). However, the mechanisms underlying effects of BQZ remain largely unknown. Osteoblast differentiation of fibroblasts plays an important role in heterotopic ossification (HO) of AS, and connexin 43 (Cx43) is crucially involved in the osteoblast differentiation of fibroblasts. The aim of the present study was to evaluate the effects of BQZ on the osteogenic differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…together with the findings summarized in Table 1, 16,77,[97][98][99][100][101][102][103][104] confirm that ASFs are target cells of BMP/TGF-β signaling and indicate that a highly activated BMP/TGF-β signal transduction pathway exists in ASFs. Concurrently, based on the evidence that the Smad6 expression is lower in ASFs than normal, it reveals the lack of self-regulation and inhibition in the BMP/TGF-β signaling of ASFs.…”
mentioning
confidence: 61%
“…together with the findings summarized in Table 1, 16,77,[97][98][99][100][101][102][103][104] confirm that ASFs are target cells of BMP/TGF-β signaling and indicate that a highly activated BMP/TGF-β signal transduction pathway exists in ASFs. Concurrently, based on the evidence that the Smad6 expression is lower in ASFs than normal, it reveals the lack of self-regulation and inhibition in the BMP/TGF-β signaling of ASFs.…”
mentioning
confidence: 61%
“…Furthermore, miR-204-5p inhibited the osteogenic differentiation of AS fibroblasts by downregulating the expression of Notch2, RUNX2 and osteocalcin. Heterotopic ossification is one of the most prominent features of AS ( 29 ), and osteogenic differentiation of fibroblasts plays a key role in the heterotopic ossification of AS ( 30 ). miRNAs play important roles in regulating cell-cell interactions between osteoclasts and fibroblasts ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the holistic concept and syndrome differentiation, TCM can be directed at different pathogenic links, using a variety of methods, and through multiple pathways, to achieve the effect of treating diseases and regulating immunity, and can alleviate the side effects of western medicine [23] . Therefore, integrated TCM and western medicine in the treatment of AS can synergize with each other to exert their own advantages, which can both remove multiple pathogenic factors of AS and improve the systemic status to achieve the best therapeutic effect [24] . At present, a host of clinical trials have shown that CHF combined with western medicine has good clinical effectiveness and safety in the treatment of AS [25] …”
Section: Introductionmentioning
confidence: 99%
“…[23] Therefore, integrated TCM and western medicine in the treatment of AS can synergize with each other to exert their own advantages, which can both remove multiple pathogenic factors of AS and improve the systemic status to achieve the best therapeutic effect. [24] At present, a host of clinical trials have shown that CHF combined with western medicine has good clinical effectiveness and safety in the treatment of AS. [25] Systematic review is the process of applying a clear methodology to find, select, and critically appraise relevant studies, from which data are extracted and combined using appropriate statistical methods to reach a comprehensive conclusion, with a view to providing evidence to address a specific clinical question.…”
Section: Introductionmentioning
confidence: 99%